Body condition of Pseudis minuta Günther, 1858 (Anura: Hylidae) inhabiting an agroecosystem from south Santa Fe Province, Argentina - Vera Candioti, Josefina (2019)
We present the first data on the body condition of P. minuta adults in a pond associated with an agroecosystem of the south Santa Fe Province, Argentina. Fieldwork was conducted from November 2012 to December 2013. Females and males did not differ in body condition, weight, nor length. However, males from December 2013 were in better condition than males from November 2012. Similarly, females from January 2013 were in better condition than those registered in November 2012. Our report provides for the first time an observation of the species in a landscape dominated by intensive agriculture in southern Santa Fe Province, corresponding to the Pampean region. Further studies should investigate habitat conditions and resources that allow the growth and development of this population of P. minuta in order to ensure its long-term permanence in the region.